Identifikasi Faktor Kritikal Pendukung dan Penghambat Implementasi Lean Construction pada Megaproyek di Indonesia (Bearing : Jurnal Penelitian dan Kajian Teknik Sipil, 2022)
Qualitatively, according to the waste in the construction sector in Indonesia, it is quite large, namely 57% when compared to the manufacturing industry which has 26% waste, the inefficiency in megaprojects is caused, among others, by too many design changes, low work expertise, delays in decision making, coordination that is not good between the parties involved, weak planning and control, delays in material delivery, and inappropriate work methods. Lean construction concept is used to eliminate waste and maximize value for users or customers. In addition, he said that the framework is a step-by-step guide in the form of a suitable guide to facilitate the implementation of the lean construction concept because the lean construction concept is a process-based concept. The purpose of this study is to identify critical factors that support and hinder the implementation of the lean construction concept in mega projects in Indonesia. In this study, a systematic literature review was used to examine the supporting factors and inhibiting factors for the implementation of lean construction. After conducting a literature review, four main supporting factors were obtained, namely managerial, labor, organizational and external. The managerial sub-factors are management commitment and Leadership Management. In addition, it was also found that the barrier factors from the implementation of lean construction were managerial, workforce, company/project organization and external. The supporting sub-factors of managerial are management commitment, management leadership, Management is unable to change existing construction concepts, Lack of training for contractors and subcontractors, misconceptions about lean construction method